Effect of Exposure on Radiographic Image Quality Based on Object Thickness on Abdominal Examination - Efrensiana Ana Melti; I Gde Antha Kasmawan; I Wayan Supardi (Buletin Fisika)
Research has been done on the effect of exposure on the quality of the radiographic image based on the thickness of the object on abdominal examination. The thickness of the object has an impact on the amount and at least the amount of exposure used, which will affect the quality of the resulting image. The data used in this study is quantitative data, namely numerical data that can be calculated. The source of data used in this study is primary data obtained directly from 28 patients through measurements of abdominal thickness, tube voltage and current and time recorded on X-ray radiographs. This study used an anteroposterior (AP) supine projection at random on abdominal examination patients from the age range of 40-60 years. The age ranges are made in three year intervals, namely 40-42, 43-45, 46-48, 49-51, 52-54, 55-57, 58-60 years. The results showed that the thicker the size of the abdomen, the use of exposure will increase. Image quality will decrease if the exposure index (IE) value is not optimum (the optimum IE value is around 1000 to 2000). In this study, the highest IE value obtained was 2189 and the lowest IE value was 965, and both values ??were not optimum. For the highest IE value (2189), the image obtained is darker in color while for the lowest IE value (965), the image obtained is white and blurry.